THE INFLUENCE OF LANGUAGE ON THE FORMATION OF SPECIALIZED TERMINOLOGY (Scientific journal of the Fergana State University, 2025)
This article is dedicated to exploring the influence of language on the formation of specialized terminology. Language plays a crucial role in the accurate and proper formation of terms used across various fields. The article discusses the importance of language elements such as morphology, syntax, and semantics in the creation of terminology, as well as the challenges in translating terms and their adaptation across languages. Furthermore, the role of context and grammatical structure in the creation of terms in different languages is highlighted. The article presents theoretical approaches and examples that demonstrate the role of language in shaping specialized or professional terminology.